PENGARUH OZON YANG DIBANGKITKAN MENGGUNAKAN REAKTOR DIELECTRIC BARRIER DISCHARGE PLASMA (DBDP) TERHADAP KONSENTRASI OKSIGEN TERLARUT, KESADAHAN, DAN pH PADA AIR MURNI - Adhi Prasetyo; Muhammad Nur; Zaenul Muhlisin; Sapto P Putro (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
A research on the application of dielectric barrier discharge reactor configured as a cylindrical spiral using ozone-producing which using the air as source and in atmospheric conditions. In this study, the observed effect of ozonation to show the influence to dissolved oxygen, pH and Calcium carbonate. Active Electrode using copper wire spiral and has pyrex to be the dielectric. Plasma produce using AC voltages of 2 kV, 10 kV, 12.5 kV and frequencies between 880 Hz to 891 Hz. Air flow rate of 1.5 L / min. At the same time ozonation, using different voltage produce different ozone concentrations. If more voltage applied, the concentration of ozone is increasing. Similarly, the measurement of dissolved oxygen concentration and Calcium carbonate. But of water pH measurements obtained tends to be stable.Keywords: Calcium carbonate, DBD reactor, dissolved oxygen, ozone, pH.